Effect of juvenility on cutting propagation of red pitaya - Lucena Cavalcante, Italo Herbert [UNESP]; Geraldo Martins, Antonio Baldo [UNESP] (Cambridge University Press, 2008)
Introduction. Pitaya (Hylocereus undatus) is an exotic fruit species little known in Brazil and which needs basic studies about plant nutrition, propagation and physiology. Emphasizing the co-existence of juvenile and adult stages in the pitaya canopy, the plant is generally propagated by cuttings. Materials and methods. A completely randomized design with four treatments and five replications was adopted. Each treatment was represented by the part of the canopy from which the cutting was taken ( upper, middle and lower cutting and cuttings from young plants). The following variables were registered: % cuttings with roots, % of live cuttings, root density, root diameter, root area, root length and root dry mass. Results were submitted to variance analyses, Tukey's test at 0.01 probability error and simple correlation analysis. Results and discussion. The results indicated that the position from which the cutting is taken had a quantitative effect on rooting formation of pitaya cuttings. Juvenile cuttings presented 35% more cuttings with roots than adult cuttings. Root density, root area, root length and root dry mass depended on juvenility, the highest results being registered for juvenile cuttings, independently of the variable. Conclusion. Juvenile and adult stages co-exist in the pitaya canopy. Juvenility is an important rooting factor for red pitaya cuttings.
Keywords: Brazil; Hylocereus undatus; vegetative propagation; propagation by cuttings; plant developmental stages; juvenility of plants; rooting